Wearable Sensors for Plants: Status and Prospects - Xuexin Yan; Yawen Pang; Kaiwen Niu; Bowen Hu; Zhengbo Zhu; Zuojun Tan; Hongwei Lei (Biosensors)
The increasing demand for smart agriculture has led to the development of agricultural sensor technology. Wearable sensors show great potential for monitoring the physiological and surrounding environmental information for plants due to their high flexibility, biocompatibility, and scalability. However, wearable sensors for plants face several challenges that hinder their large-scale practical application. In this review, we summarize the current research status of wearable plant sensors by analyzing the classification, working principles, sensor materials, and structural design and discussing the multifunctional applications. More importantly, we comment on the challenges the wearable plant sensors face and provide our perspectives on further improving the sensitivity, reliability, and stability of wearable plant sensors for future smart agriculture.